Políticas educacionais: um estudo sobre o ensino médio nos municípios da região do Baixo Tocantins - SILVA, Rayana Barros da (2022)
The reflections contained here aim to present the research work developed by the Study, Research and Extension Group, Society, State, Education: emphasis on municipal governments and rural education - GEPESEED, from the Institutional Scholarship Program of Scientific Initiation – PIBIC/UFPA CAMPI DO INTERIOR, which aimed to to investigate how public high school educational policies are implemented in the formation of students from the countryside and the city, in state public schools, in the municipalities of Abaetetuba, Barcarena, Concordia do Pará, Moju and Tomé-Açu. From the study of legislation, theoretical bases and analysis of empirical data, it became possible to establish understandings about the mediations that are established in the implementation of educational policies for the high school stage. In this sense, the study pointed to the need for the policy educational system to consider aspects of the region, such as a socio-educational and political space, where conception of education guarantees the autonomy of education systems to formulate their pedagogical political projects, with community participation in the construction process of these regulations, aiming to provide students with a school that guarantee the reference in values ​​and principles guided not only in the work, but also, on citizenship and diversity.